PENGARUH GAYA HIDUP, PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONLINE SHOPEE - MEGA SIFTI MINARTI; NORA PITRI NAINGGOLAN (LP2MTBM MAKARIOZ, 2020)
This study discusses lifestyle, promotion, service quality on purchasing decisions at online shopee shops. The samplingmethod uses nonprobality sampling technique with the type of purposive sampling with respondents keriteria are consumerswho have made purchases at online shopee shops as many as 100 respondents. The technique of collecting data usinginstruments used as a questionnaire. The data quality test in this study used the validity and reliability test, the classicalassumption test and the influence test in this study using multiple linear regression analysis and coefficient of determinationanalysis (R2), as well as the hypothesis testing in this study using (t test) and (f test ) using the SPSS software programversion 22. The results of the coefficient of determination (R2) obtained from the lifestyle, promotion and quality of servicevariables obtained amounted to 0.496 (49.6%). The results of multiple linear regression showed Lifestyle (X1) of 0, 2630(26.3%) to the purchase decision (Y), and Promotion (X) determined 0.3968 (39.7%) to the purchase decision (Y), andservice quality (X3) of 0.2000 (20)%) on purchasing decisions (Y). From the t test and f test, it can be concluded that lifestylehas a significant effect on purchasing decisions, promotion determines partial significance of purchasing decisions, andservice quality is significantly related to purchase decisions, and lifestyle, promotion, and service quality togethersimultaneously make significant decisions simultaneously to the purchase decision at an online shopee shop.